Comparison of natural and artificial vasopressin deficiency: why the latter is lethal? - D. Zelena (Вавиловский журнал генетики и селекции)
The transgenic mouse technology is widespread, however, untill now 22.0 % of tested null mutations was found to be lethal. The complete lack of vasopressin (AVP) resulted also in preweaning lethality. It is surprising take into consideration the viability of the AVP mutant Brattleboro rats. Thus, AVP is essential for survival, but which of its ubiquiter role is the most important. AVP exerts its effect through specific plasma membrane receptors. V1a receptors can induce vasoconstriction maintaining blood pressure during hypovolemia. The V1b receptor on the anterior pituitary has a role in stress adaptation. The V2 subtype is located in the kidney and contributes to the antidiuresis. The avp gene consists of a signal peptide, AVP, neurophysin 2 and a C-terminal glycopeptide. The naturally occuring AVP-deficient Brattleboro rat has a framshift mutation in the neurophysin portion resulting in cental diabetes insipidus. In its hypothalamus AVP is not produced, while in certain peripheral tissues it may be expressed, suggesting the existence of a different synthetic pathway. The avp knockout mice can also be produced, they will be born, but without peripheral AVP administration they will not survive. Comparing available knockout models we can conclude that the combined V1a and V2 receptor mediated effects, namely hypotension and water lost together may led to lethality. As in Brattleboro and targetted knockout mice the local synthesis of AVP in the heart can be maintained and AVP can be released into the general circulation. Thus, in these animals vasoconstriction can compensate the hypovolemia.